2017
DOI: 10.1111/cch.12484
|View full text |Cite
|
Sign up to set email alerts
|

Child understandings of the causation of childhood burn injuries: Child activity, parental domestic demands, and impoverished settings

Abstract: Background: Burns are a global public health problem. In South Africa, the rate of paediatric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…It is uncertain why some of the individual subtypes of physical neglect had a stronger or weaker association with PEs. For example, in terms of the association observed between being made to do chores that were too difficult or dangerous and significantly higher odds for PEs even after adjusting for other forms of physical neglect, it is possible that this form of early life neglect may have placed the child in a situation where there was an increased risk of having an accident or being injured (Titi, van Niekerk, & Ahmed, 2018). This might be important as other research has linked injury and the potential trauma associated with it to higher odds for PEs both in low‐ and middle‐income countries and the United States.…”
Section: Discussionmentioning
confidence: 99%
“…It is uncertain why some of the individual subtypes of physical neglect had a stronger or weaker association with PEs. For example, in terms of the association observed between being made to do chores that were too difficult or dangerous and significantly higher odds for PEs even after adjusting for other forms of physical neglect, it is possible that this form of early life neglect may have placed the child in a situation where there was an increased risk of having an accident or being injured (Titi, van Niekerk, & Ahmed, 2018). This might be important as other research has linked injury and the potential trauma associated with it to higher odds for PEs both in low‐ and middle‐income countries and the United States.…”
Section: Discussionmentioning
confidence: 99%
“…One study interviewed children in South Africa to investigate their understanding of the causes of childhood burns. Themes that appeared from the interviews centered around unsafe living structures (lack of electricity, overcrowded housing) or inadequate supervision and compromised caregiving (inebriated parent, parent leaves home after lighting the stove) [53]. A retrospective chart review of patients in the southwest US with injuries to their total body surface area (TBSA) >15% found that socioeconomic status (determined by zip code and US census data) was only associated with increased burn risk in patients who identified as women [54].…”
Section: Economic Stabilitymentioning
confidence: 99%